AJTE 2017
DOI: 10.14221/ajte.2017v42n3.3
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Emotion and Learning as Praxis: Professional Development that Matters

Abstract: This ethnographic study analyses the diverse emotions emerging within one teacher professional development workshop that engaged teachers as creative writers. Participating teachers revealed a vibrant range of positive and negative emotions as they worked within institutional discourses that conflicted with their intrinsic beliefs about effective teaching. They revealed their emotional investment in their roles and their desires for meaningful practice in spite of pressures to abide by managerial practices. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 20 publications
(29 reference statements)
2
30
0
Order By: Relevance
“…She found that hope, along with attribution and emotions, predicts to some extent successful performance expectations in mathematics. In another study, Yoo and Carter (2017) found hope and vulnerability in teachers' reflections about their mathematics professional development. They suggest that in order to cultivate positive emotional growth amongst teachers in relation to mathematics, that the acknowledgement of the complexity of emotional identity is necessary.…”
Section: Hopementioning
confidence: 94%
See 1 more Smart Citation
“…She found that hope, along with attribution and emotions, predicts to some extent successful performance expectations in mathematics. In another study, Yoo and Carter (2017) found hope and vulnerability in teachers' reflections about their mathematics professional development. They suggest that in order to cultivate positive emotional growth amongst teachers in relation to mathematics, that the acknowledgement of the complexity of emotional identity is necessary.…”
Section: Hopementioning
confidence: 94%
“…Emotions are intrinsic to teaching: they are an essential part of the teacher-student relationship, central to teachers' investment in their practice and significantly impact behaviour (Stephanou, 2012;Yoo & Carter, 2017). More specifically, emotions play a central role in pre-service teachers' experiences of learning mathematics (Bailey, 2014;Loughran, 2013).…”
Section: Mathematics Beliefs and Emotionsmentioning
confidence: 99%
“…Generally, teachers in face-to-face teaching observe student expressions to determine whether they actively engaged their learning (Yelinek & Grady, 2017;Yoo & Carter, 2017). But this treatment is frequently inaccurate and leads to increasing the burden on teachers.…”
Section: Classroommentioning
confidence: 99%
“…This line of research brought us to examine the relationships among teacher emotions, education, and learning because a reform is always a request for a change in teaching practices and for teachers to learn new things (Shoffner, 2008;Yoo & Carter, 2017).…”
Section: Emotions In Teaching and Teacher Educationmentioning
confidence: 99%
“…Still, the teacher also exhibited positive emotions when he came across opportunities to improve his teaching and reinforce his professional identity. Yoo and Carter (2017) carried out an ethnographic study in the form of a professional development program focused on creative writing and writing practices. They identified four different types of emotions that the participants experienced: (1) energy, excitement, and passion; (2) inner conflict, frustration, and discouragement; (3) vulnerability, engagement, and hope; and (4) generosity, gratitude, and inspiration.…”
Section: Emotions In Teaching and Teacher Educationmentioning
confidence: 99%